1993
DOI: 10.1042/cs0840675
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Cyclosporin a Absorption in Rat Small Bowel and the Effect of Bile

Abstract: 1. Cyclosporin A absorption was examined after the instillation of approximately 2 mg/kg into four segments (mean length 15 cm) of rat small bowel, isolated in situ in fed Wistar female rats: SI (duodenum and proximal jejunum distal to the common bile duct); SII (distal jejunum); SIII (proximal ileum) and SIV (distal ileum). 2. Cyclosporin A concentrations in whole blood were assayed by an enzyme-mediated immunoassay for up to 4 h in samples drawn from the femoral vein and used to determine the following pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 0 publications
3
6
0
Order By: Relevance
“…In contrast, CYP3A was expressed more strongly in the upper intestine than in the lower intestine in terms of both protein level and metabolic activity, and it was more strongly induced by dexamethasone in the lower intestine than in the upper intestine. These findings represent a significant extension of our previous study [21], and we confirmed that cyclosporin A was absorbed predominantly from the upper intestine in mice, as reported by Cakaloglu et al [35].…”
Section: U N C O R R E C T E D P R O O Fsupporting
confidence: 92%
“…In contrast, CYP3A was expressed more strongly in the upper intestine than in the lower intestine in terms of both protein level and metabolic activity, and it was more strongly induced by dexamethasone in the lower intestine than in the upper intestine. These findings represent a significant extension of our previous study [21], and we confirmed that cyclosporin A was absorbed predominantly from the upper intestine in mice, as reported by Cakaloglu et al [35].…”
Section: U N C O R R E C T E D P R O O Fsupporting
confidence: 92%
“…In the present study, examination of the absorption of CsA revealed that CsA was absorbed predominantly from the upper intestine, which was consistent with the findings of previous studies (Cakaloglu et al, 1993;Jin et al, 2006). Increased plasma concentrations of CsA in the nephrotic rats compared with the control rats indicates that the first-pass effects on CsA absorption by the intestine and liver decreased in the nephrosis model.…”
Section: Increased Absorption Of Cyclosporine a In A Nephrosis Modelsupporting
confidence: 80%
“…UDCA administration also induced no significant improvements in relative cyclosporin bioavailability in the five patients with Roux-en-Y enterostomy in this series. Such interventions reduce cyclosporin absorption because of the reduced length of bowel available for absorption [24], and recent experimental studies suggest that bile improves cyclosporin absorption in both the proximal and distal small intestine [3], so benefit with UDCA may have been expected. Chenodeoxycholate has been suggested to improve cyclosporin absorption by promoting micelle formation [4] and the weaker micelle-forming Rroperties of UDCA [19] may underlie its lesser potency.…”
Section: Discussionmentioning
confidence: 99%